Sytuacja mieszkaniowa rodzin pracowników państwowego sektora rolnego (na przykładzie wybranych województw) - Berndt-Kostyrzewska, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
The aim of the research conducted in the years 1993-1995 was to determine the standards of useful floor space and technical standards of flats occupied by families of farmer employees of state owned farms (PGR). The research was based on a survey carried out in six voivodships: białostockie, olsztyńskie, jeleniogórskie, wałbrzyskie, koszalińskie and słupskie. The required data was extracted from the special questionnaires which were the main tool of the direct interviews. Studies reveal different standard of dwellings according to the year they were completed. Such indicators as useful floor space per person and level of household furnishing with selected durables were Iower in olsztyńskie voivodship by comparing them with an average in dwellings population under the survey.